Motivating young adults to connect with nature for stress relief: A study in Taiwan during the COVID-19 pandemic - Yeung, Yin-Yan; Yu, Chia-Pin (Frontiers in Psychiatry, 2022)
It is known exposure to and connectedness with nature is beneficial for psychological wellbeing and stress relief. However, many factors hinder people, including young adults, from utilizing natural resources for healing. The present study indicates using a motivational enhancement approach and additional motivational elements in public messaging to address ambivalence towards nature exposure successfully results in favorable impacts on belief, intention, recall of positive nature elements, and perceived stress. Because this study coincided with the development of the COVID-19 pandemic in Taiwan, it offers a valuable opportunity for exploring how effective the motivational indicators were at different stages of the pandemic, as well as how connectedness to nature can explain perceived stress. In measuring motivation, we captured the essential elements of mobilizing young adults to connect with nature while also exploring potential expansion of behavioral indicators. We discuss how to foster inspiration during a pandemic to enhance connectedness to nature.